Teletrabalho: desafio ao Direito do Trabalho e as modificações trazidas com a reforma trabalhista - Massaro, Rubens Luiz Schmidt Rodrigues (2020)
Teleworking is a new form of work that captures the attention of the entire society and economy, due to its proposal to break physical and geographical limits, to reduce expenses and to make working conditions more flexible. It resulted from a sum of factors such as the advancement of information and communication technologies, the growth of the organizational philosophy of toyotism, globalization and the rise of the ideology of neoliberalism. In an environment of post-industrial society, Fourth Industrial Revolution, significant changes in the division of labor and productive restructuring, the world was emerging in a very strong futuristic vortex. Indeed, due to its particularities, Labor Law based on the concepts arising from the First Industrial Revolution and the organizational philosophies of taylorism and fordism needed a legislative update to improve the efficiency of its principles. It so happens that, until then, the application of the law in the case of teleworking was based on doctrines and jurisprudence, which had many schisms among themselves, which caused a great legal uncertainty. However, this was the opportunity for many neoliberal movements to prepare a revisionary effect on Labor Law based on the precepts of the Welfare State, that is, on the State's intervention in labor relations and on protectionism for workers. In Brazil, this neoliberal movement is represented by the Labor Reform (Law nº 13.467/2017), involved in many controversies and criticisms, being responsible for bringing the new regulation of teleworking. As it could not be otherwise, its conception was met with much criticism. The regulation of teleworking by the Labor Reform brought both positive and negative points, the latter with very harmful potential for the dignity of workers. It is essential to carry out an analysis of these provisions, always in line with the fundamental rights of workers and the principles of Labor Law. This dissertation seeks, in summary, to explain what telework is in its abstract concept, the scenario in which it developed, outline its legal concept, analyze the innovations arising from the Labor Reform and, finally, provide an overview of the challenges to Law Labor that the telework regulation carries. The development of the dissertation will rely on the interdisciplinarity of sociology and economics. The legal study will have doctrinal, jurisprudential and comparative law resources